Examining the relationship between training load and both performance and injury risk in Australian Football - Harrison, P. W.; Johnston, D. R. D.; Quain, D. (Journal of Australian Strength and Conditioning, 2018)
A significant amount of research has examined the relationship between training load and injury, identifying patterns that increase injury risk. However, little research in Australian Football has examined training load and performance. The purpose of this study was to review the literature examining the training load-injury and the training load-performance relationships.